Una Messa ‘propria’ per i santi Faustino e Giovita: il ms. alfa del Museo Diocesano di Arte Sacra a Brescia - Vitale, Stefania (Scrineum, 2013)
There is now new evidence which allows us to detect in the Gradual MS Museo Diocesano di Arte Sacra, Brescia, Codici Miniati , alfa, one of the choir books made in the late Middle Ages (XV ex - XVI in centuries) expressly for the Benedictine monastery of San Faustino Maggiore in Brescia. Being the fruit of the spiritual and cultural rebirth which affected the monastery in the fifteenth century and later revealed itself through the fusion with the S. Giustina di Padova Congregation (1490), the Gradual preserves a precious treasure, a proprium Mass for the saints Faustino and Giovita, the musical transcription of which is given in the appendix, together with the codicological description of the manuscript, the table of contents and some comparative tables.